Highly interconnected inverse opal extracellular matrix scaffolds enhance stem cell therapy in limb ischemia. (1st July 2021) - Li, Wen; Bai, Yanli; Cao, Jiasong; Gao, Shan; Xu, Pan; Feng, Guowei; Wang, Lichen; Wang, Hongjun; Kong, Deling; Fan, Meng; Zhang, Jun; Zhu, Meifeng
Abstract: The therapeutic effectiveness of cell transplantation in treatment of diseases and injuries is often limited by low cell retention, survivability, and engraftment. Extracellular matrix (ECM)-derived scaffolds are capable of controlling cell responses, thereby offering potential solutions to current challenges associated with cell therapy. However, it remains a technical challenge to produce ECM scaffolds with highly interconnected porous structure specifically required for cell transplantation. Here, we developed inverse opal porous extracellular matrix (ioECM) scaffolds through subcutaneous implantation of sacrificial templates assembled from polymer microspheres, followed by removal of the microsphere template and cellular content. Such highly interconnected porous ioECM scaffolds supported the anchorage, survival, viability, anti-apoptotic and paracrine activities of rat bone marrow mesenchymal stem cells (BMSCs), which further promoted endothelial cell migration and tube formation and viability. Upon transplantation into nude mouse critical limb ischemic model, ioECM promoted the engraftment of laden BMSCs, facilitated interconnected vascular network formation with accelerated recovery of blood perfusion and inhibited muscle atrophy and fibrosis. Our study demonstrates a unique strategy to engineer highly porous yet well-interconnected ECM scaffolds specifically for cell transplantation with marked improvement of survivability and vascularization, which offers an essential step toward the success of cell therapy and regenerative medicine. Statement of significance: Cell-based therapy has a good developing foreground applied in a variety of tissue regeneration. Extracellular matrix (ECM) scaffolds is an optimal choice for cell delivery duo to its superior biocompatibility and favorable immune responses. However,  the current ECM scaffolds lacking of the controllable pore structure restrict the cell delivery efficiency and therapeutic outcome. Here, we fabricated highly interconnected inverse opal extracellular matrix (ioECM) scaffolds, which can enhance the effect of stem cell therapy in limb ischemic model by improving the survival, viability, and paracrine activities of stem cells. Our study provides reference value for the design and fabrication of ECM based biomaterials for cell transplantation. Graphical abstract: Image, graphical abstract